The Optimal First-Line Therapy of Helicobacter pylori Infection in Year 2012 - Kuo, Chao-Hung (Hindawi Publishing Corporation, 2012)
This paper reviews the literature about first-line therapies for H. pylori infection in recent years. First-line therapies are facing a challenge because of increasing treatment failure due to elevated antibiotics resistance. Several new treatment strategies that recently emerged to overcome antibiotic resistance have been surveyed. Alternative first-line therapies include bismuth-containing quadruple therapy, sequential therapy, concomitant therapy, and hybrid therapy. Levofloxacin-based therapy shows impressive efficacy but might be employed as rescue treatment due to rapidly raising resistance. Rifabutin-based therapy is also regarded as a rescue therapy. Several factors including antibiotics resistance, patient compliance, and CYP 2C19 genotypes could influence the outcome. Clinicians should use antibiotics according to local reports. It is recommended that triple therapy should not be used in areas with high clarithromycin resistance or dual clarithromycin and metronidazole resistance.